Hodgkin Lymphoma Monozygotic Triplets Reveal Divergences in DNA Methylation Signatures - Xia, Chuanyou; Olsen, Thale Kristin; Zirakzadeh, A. Ali; Almamoun, Radwa; Sjöholm, Louise K.; Dahlström, Jenny; Sjöberg, Jan; Claesson, Hans-Erik; Johnsen, John Inge; Winqvist, Ola; Xu, Dawei; Ekström, Tomas J.; et al. (Frontiers in Oncology, 2020)
We studied DNA-methylation profiles in four different cell populations from a unique constellation of monozygotic triplets in whom two had developed Hodgkin Lymphoma (HL). We detected shared differences in DNA-methylation signatures when comparing the two HL-affected triplets with the non-affected triplet. The differences were observed in naïve B-cells and marginal zone-like B-cells. DNA methylation differences were also detected when comparing each of the HL-affected triplets against each other. Even though we can not determine whether treatment and/or disease triggered the observed differences, we believe our data is important on behalf of forthcoming studies, and that it might provide important clues for a better understanding of HL pathogenesis.